On the genus Hermippus Simon, 1893 (Araneae: Zodariidae, Zodariinae) in India with the description of three new species from the Western Ghats and proposing a new biogeographical hypothesis for the distribution of the genus - Sankaran, Pradeep M.; Jobi, Malamel J.; Joseph, Mathew M.; Sebastian, Pothalil A. (Zootaxa, 2014)
Three new species of the ant-eating spider genus Hermippus Simon, 1893, H. globosus sp. nov., H. inflexus sp. nov. and H. gavi sp. nov. are described and illustrated from the Western Ghats in the Kerala region of southern India. The genus is redefined and two species groups are recognized: the cruciatus-group with all the five described Oriental species including H. cruciatus Simon, 1905, H. arjuna Gravely, 1921, H. inflexus sp. nov., H. globosus sp. nov. and H. gavi sp. nov. and the loricatus-group representing all the seven described Afrotropical species including H. loricatus Simon, 1893, H. affinis Strand, 1906, H. schoutedeni Lessert, 1938, H. septemguttatus Lawrence, 1942, H. minutus Jocqué, 1986, H. tenebrosus Jocqué, 1986 and H. arcus Jocqué, 1989. The biogeographic distribution and possible migratory route of Hermippus spp. from Africa to the Oriental region are given.